Propellant Development Using Local Sources of Nitrate Compounds - Suharnoko, Suharnoko; Sopamena, Chairussani Abbas; Jasmansyah, Jasmansyah; Murniati, Anceu; Hardian, Arie (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2023)
Currently in Indonesia, propellant research is still rarely carried out due to bureaucratic and budgetary problems. This study aimed to determine the optimum composition of propellant using local sources of nitrate compounds based on its combustion heat value and to study the effect of the composition on its combustion heat value. The propellant composition used in this study consists of oxidizing agents (local nitrate compounds), fuel (Aluminium), binder (polyester-based resin), and additive (catalyst). A bomb calorimetry method (ASTM D5865/5865-19) was used to determine the combustion heat value of the propellant. The results showed that the heat of combustion of local content nitrate compound-based propellants was high (> 1500 cal/g), adding binder to the propellant composition increases the heat of combustion. Ammonium nitrate-based propellant has the highest heat of combustion value of 3,788 cal/g. The optimum binder composition in the propellant was 33% (w/w). Based on this study, local source of nitrate compounds has potential to be used for development of propellant, especially in Indonesia. Therefore, it can encourage rocket research in Indonesia as a capital for the development of defense equipment to be less expensive.